The Influence of Competence and Work Motivation on Employee Performance at PT Mitra Koleksi Mandiri Tangerang - Sari, Shella Puspita; Tasik, Rina Bura (Sean Institute, 2025)
This study aims to examine the influence of competence and work motivation on employee performance at PT Mitra Koleksi Mandiri Tangerang. The research adopts a quantitative method with an associative approach and utilizes a saturated sampling technique. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, regression analysis, correlation coefficient, and hypothesis testing. The results reveal that employee competence significantly influences performance, indicating that knowledge, skills, and attitude play a critical role in shaping work outcomes. Similarly, work motivation is found to have a significant impact on employee performance, particularly in aspects related to recognition, security, and working conditions. When tested simultaneously, competence and motivation jointly contribute to improving employee performance with a very strong level of correlation. The study highlights the importance of developing employee competencies and maintaining motivational drivers to enhance productivity and achieve organizational goals. These findings offer valuable insights for human resource management practices in the service sector.